Teaching Tolerance To The Future English Teachers At Islamic English Education Study Program Through Sufism Morals Course - Muhammad Alief Raihan Ramadhan; Zaitun Qamariah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This literature review explores strategies for teaching tolerance through Sufism moral (Akhlak Sufism) courses for future English teachers in the Islamic English Education Study Program. The morals of Sufism, as part of the Islamic tradition, emphasize the development of moral and spiritual character which is essential to forming a tolerant and inclusive attitude. In the context of teacher education, the integration of Sufism values ​​aims to increase the understanding and application of tolerance among prospective teachers, so that they can act as agents of positive change in a multicultural environment. This article reviews relevant literature to identify the methods, challenges, and impacts of implementing Sufism Morals in the English teacher education curriculum. Findings show that this approach not only enriches prospective teachers' pedagogical competencies but also shapes attitudes that are more inclusive and respectful of diversity.